2018
DOI: 10.1111/jep.13013
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a medicines management model on medication‐related readmissions in older patients admitted to a medical acute admission unit—A randomized controlled trial

Abstract: This study showed that a clinical pharmacist can be used to identify and solve medication-related problems, but this study did not find any effect on the selected outcomes. The frequency of medication-related readmissions was low, leaving little room for improvement. Future research should consider other study designs or outcome measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
53
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(61 citation statements)
references
References 36 publications
(43 reference statements)
8
53
0
Order By: Relevance
“…Twelve studies scored low in all five risks of bias domains [ 24 , 25 , 28 , 34 , 35 , 38 , 41 , 42 , 44–47 ] (see Supplementary Material A4 ). Nine studies were rated as having the highest risk of bias [ 26 , 27 , 29 , 31 , 33 , 37 , 39 , 40 , 43 ] based on randomisation and allocation concealment methods.…”
Section: Resultsmentioning
confidence: 99%
“…Twelve studies scored low in all five risks of bias domains [ 24 , 25 , 28 , 34 , 35 , 38 , 41 , 42 , 44–47 ] (see Supplementary Material A4 ). Nine studies were rated as having the highest risk of bias [ 26 , 27 , 29 , 31 , 33 , 37 , 39 , 40 , 43 ] based on randomisation and allocation concealment methods.…”
Section: Resultsmentioning
confidence: 99%
“…One study found that point-of-care assessment led to a higher proportion of successful discharges in four hospitals [28], while another study found that hospital costs had an impact on the overall increase in successful discharges [29]. Otherwise, pre-discharge planning was not found to affect readmission rates [30,31,32,33,34] although it was associated with slight improvements in quality of life [27,32] and increased patient understanding of their treatment [32,35]. A systematic review by Ogilvie (2005) found that having acute medical assessment units for children within the hospital, enabled children to be admitted less and had lower rates of readmission [36].…”
Section: Resultsmentioning
confidence: 99%
“…The data provided in this study were obtained from a pool of 400 patients who all took part in the intervention arm of a randomized controlled trial conducted by one of the authors (TG) at the Hospital of South West Jutland from April 2013 to December 2014. 19 The SMP was launched at the hospital on 24 February 2014. Patients included in the randomized controlled trial were acutely admitted medical patients aged 65 years or above, whereas extremely ill, isolated and terminal patients, patients without a Danish social security number and patients unable to give informed consent were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…A full description of the intervention is described elsewhere, 19 but described briefly here. During the reconciliation, the clinical pharmacist reviewed the electronic hospital patient record, SMP and correspondence notes from nursing homes and general practitioners when available.…”
Section: Methodsmentioning
confidence: 99%